Effect of molasses on the chemical characteristics of seaweed-based organic fertiliser. Issue 1 (April 2021) - Nurhayati,; Cahyaningtyas, W; Kusumawati, R; Basmal, J
Abstract: Organic fertiliser is one of the essential factors needed in natural farming. Seaweed can be used as raw material for making organic fertilisers because it contains complete growth hormones, macro, and micronutrients for plant growth. The formulation of seaweed and silage for organic fertiliser has low levels of C-organic, so other materials are needed, for example, molasses. Addition of molasses in organic fertiliser formulations carried out to evaluate the optimum molasses concentration and study the chemical characterisation of organic fertilisers. The chemical characteristics measured were moisture content, ash content, potassium content, C-organic, N-total, and C/N ratio. The results showed that an increase in molasses concentration led to an increase in the moisture and C-organic content, and C/N ratio. The addition of 26% molasses (PTB2) was the best treatment, resulting in fertiliser with a moisture content of 6.37%, 30.01% ash content, 0.83% N-total, 0.04% potassium content, 37.58% C-organic, and 44.93 C/N ratio.